Using Ontologies to aid Knowledge Sharing in HCI Design - Castro, Murillo V. H. B.; Barcellos, Monalessa P.; Falbo, Ricardo de A.; Costa, Simone D. (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2021: Anais do XX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2021)
Developing interactive systems is a challenging task that involves concerns related to the human-computer interaction (HCI), such as usability and user experience. Therefore, HCI design is a core issue when developing such systems. It often involves people with different backgrounds (e.g., Arts, Software Engineering, Design), which makes knowledge transfer a challenging issue. Ontologies have been acknowledged as a successful approach to represent domain knowledge and support knowledge-based solutions. Hence, in this work, we propose to explore ontologies to represent structured knowledge and improve knowledge sharing in HCI design. We briefly present the Human-Computer Interaction Design Ontology (HCIDO), a reference ontology that addresses HCI design aspects that connect HCI and Software Engineering concerns. By making knowledge related to the HCI design domain explicit and structured, HCIDO has helped us to develop KTID, a tool that aims to support capturing and sharing useful knowledge to aid in HCI design. Preliminary results indicate that the tool may be particularly useful for novice HCI designers.